Measuring Sexual Violence on Campus: Climate Surveys and Vulnerable Groups. (3rd April 2017) - de Heer, Brooke; Jones, Lynn
ABSTRACT: Since the 2014 Not Alone report on campus sexual assault, the use of climate surveys to measure sexual violence on campuses across the United States has increased considerably. The current study utilizes a quasi meta-analysis approach to examine the utility of general campus climate surveys, which include a measure of sexual violence, in comparison to sexual assault specific climate surveys, in measuring student sexual assault experiences. Past research has highlighted the need to not only understand campus sexual assault prevalence rates for the general student population, but also the specific risk posed to more vulnerable populations such as the lesbian, gay, bisexual, questioning/queer community (LGBQ) and Native American students. Results indicate that general campus climate surveys may be underestimating both the sexual victimization of the general student body as well as that of LGBQ and Native American students. Research and policy recommendations that focus on improved measurement of campus sexual assault experiences are discussed.